THE LATEST TECHNOLOGIES IN THE PRODUCTION OF VODKA - Двірко, Анна; Бойко, Петро (SWorldJournal, 2024)
The article presents the current trends in the development of the liquor and vodka industry of Ukraine. The results of the scientists' research for the improvement of water preparation and purification of the water-alcohol mixture (sorting) in the produc